Structural Shrinking and Rotation Decrease Quasi Surface Tension for Polar CeO2(100). Issue 8 (21st June 2022) - Zhou, Hui; Wu, Xin‐Ping; Gong, Xue‐Qing
Abstract: Surfaces determine many important physicochemical properties of the solid materials, and the polar surfaces are particularly appealing for their unusual characteristics as they are intrinsically unstable and always reconstruct to compensate for the surface polarity. In this work, by performing density functional theory calculations corrected by on‐site Coulomb interactions (DFT+U), it is determined that for polar CeO2 (100), besides the classical O‐t, Ce‐t, and CeO4 ‐t types of reconstruction, a series of novel "pocket‐like" structures can give significantly better stabilities. It is proposed that the shrinking effect caused by the pocket formation can effectively reduce the surface tension, and specifically, promote the rotation of the CeO4 units at CeO4 ‐t‐p surface to further stabilize the edge Ce cations of the units. Such CeO4 ‐t‐p reconstructed CeO2 (100) can also act as a promising support for the single metal atoms since the induced shrinking and rotation effects can further promote their adsorption and dispersion. This work provides new models to help understand surface reconstruction and adsorption. Abstract : The present study shows that the novel "pocket‐like" structures can give rise to better stabilities than classical O‐t and CeO4 ‐t reconstructions for the polar CeO2 (100) surface, which can be attributed to the shrinking effect caused by the pocket formation and the induced rotation of the surface structural units. Such property may even help the adsorption and dispersion of single metal atoms.